The expanding world Ayahuasca diaspora : appropriation, integration, and legislation - Labate, Beatriz Caiuby; Cavnar, Clancy (Vitality of indigenous religions., 2018)
"During its expansion from the Amazon jungle to Western societies, ayahuasca use has encountered different legal and cultural responses. Following on from theearlier edited collection, The Expanding World Ayahuasca Diaspora continues to explore how certain alternative global religious groups, shamanic tourism industries and recreational drug milieus grounded in the consumption of the traditionally Amazonian psychoactive drink ayahuasca embody various challenges associated with modern societies. Each contributor explores the symbolic effects of a "bureaucratization of enchantment" in religious practice, and the "sanitizing" of indigenous rituals for tourist markets. Chapters include ethnographic investigations of ritual practice, transnational religious ideology, the politics of healing and the invention of tradition. Larger questions on the commodification of ayahuasca and the categories of sacred and profane are also addressed. Exploring classic and contemporary issues in social science and the humanities, this book provides rich material on the bourgeoning expansion of ayahuasca use around the globe. As such, it will appeal to students and academics in religious studies, anthropology, sociology, psychology, cultural studies, biology, ecology, law and conservation."--Provided by publisher